The present and future of insect biodiversity conservation in the neotropics: policy gaps and recommendations - Duffus, NE; Echeverri, A; Dempewolf, L; Noriega, JA; Furumo, PR; Morimoto, J (Springer, 2023)
Emerging evidence suggests that insect populations may be declining at local and global scales, threatening the sustainability of the ecosystem services that insects provide. Insect declines are of particular concern in the Neotropics, which holds several of the world’s hotspots of insect endemism and diversity. Conservation policies are one way to prevent and mitigate insect declines, yet these policies are usually biased toward vertebrate species. Here, we outline some key policy instruments for biodiversity conservation in the Neotropics and discuss their potential contribution and shortcomings for insect biodiversity conservation. These include species-specific action policies, protected areas and Indigenous and Community Conserved Areas (ICCAs), sectoral policies, biodiversity offsetting, market-based mechanisms, and the international policy instruments that underpin these efforts. We highlight that although these policies can potentially benefit insect biodiversity indirectly, there are avenues in which we could better incorporate the specific needs of insects into policy to mitigate the declines mentioned above. We propose several areas of improvement. Firstly, evaluating the extinction risk of more Neotropical insects to better target at-risk species with species-specific policies and conserve their habitats within area-based interventions. Secondly, alternative pest control methods and enhanced monitoring of insects in a range of land-based production sectors. Thirdly, incorporating measurable and achievable insect conservation targets into international policies and conventions. Finally, we emphasise the important roles of community engagement and enhanced public awareness in achieving these improvements to insect conservation policies.